(untitled) (Journal of Scientific Research, 2024)
In this paper, an attempt has been made to develop a model as Inflated form of zero truncated Poisson Ailamujia distribution. The proposed model involved two parameters, estimated by the maximum likelihood estimation method and derived as an expression of the Fisher Information Matrix. To evaluate the adequacy and applicability of the proposed model, it is applied to real data sets on child mortality and genetic count data.